Self-Financed Wagering Mechanisms for Forecasting - Lambert, Nicolas; Langford, John; Vaughan, Jennifer Wortman; Chen, Yiling; Reeves, Daniel; Shoham, Yoav; Pennock, David (Ninth ACM Conference on Electronic Commerce (EC), 2008)
We examine a class of wagering mechanisms designed to elicit truthful predictions from a group of people without requiring any outside subsidy. We propose a number of desirable properties for wagering mechanisms, identifying one mechanism—weighted-score wagering—that satisfies all of the properties. Moreover, we show that a single-parameter generalization of weighted-score wagering is the only mechanism that satisfies these properties. We explore some variants of the core mechanism based on practical considerations.